Ironfounding production in the second half of the XVIII – XIX centuries (on the example of Temnikov district of Tambov province) - E. N. Bikeikin; T. M. Guseva; G. A. Kursheva; S. V. Pershin (Вестник Самарского университета: История, педагогика, филология)
Modern economic problems have generated increased interest among researchers in the problems of economic development of pre-revolutionary Russia and its individual regions. In the second half of the XVIII century, an industry not typical for the region – ferrous metallurgy – was developing on the territory of modern Mordovia. The purpose of this article is to analyze the activities of iron founding and ironworks during their formation in the second half of the XVIII century and development in the XIX century. To achieve this goal, it is necessary to solve the following tasks: establish the dynamics of the development of manufactories; identify the features typical for enterprises in a given area; show their structure and degree of mechanization; consider the situation of workers. Scientific novelty is determined by the insufficient study of the issues determining the nature and pace of the processes of formation and development of ferrous metallurgy, taking into account regional characteristics. The source base of the study was made up of published sources, such as News of Scientific Archival Commissions, Commemorative Books, Journals of Manufactories and Trade. As a result, the following conclusions were made: iron founding and ironworks created on the territory of the city and county were an important component of the economic development of the region; the ore that was mined in this area had a low iron content, so the main reasons for the creation of such enterprises in the second half of the XVIII century on the territory of modern Mordovia were the excess of wood fuel needed for smelting metal, and cheap labor.